Energy and exergy performance assessment of a novel solar-based integrated system with hydrogen production. (12th July 2019) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Abstract: In this study, a new solar power assisted multigeneration system designed and thermodynamically analyzed. In this system, it is designed to perform heating, cooling, drying, hydrogen and power generation with a single energy input. The proposed study consists of seven sub-parts which are namely parabolic dish solar collector, Rankine cycle, organic Rankine cycle, PEM-electrolyzer, double effect absorption cooling, dryer and heat pump. The effects of varying reference temperature, solar irradiation, input and output pressure of high-pressure turbine and pinch point temperature heat recovery steam generator are investigated on the energetic and exergetic performance of integration system. Thermodynamic analysis result outputs show that the energy and exergy performance of overall study are computed as 48.19% and 43.57%, respectively. Moreover, the highest rate of irreversibility has the parabolic dish collector with 24, 750 kW, while the lowest rate of irreversibility is calculated as 5745 kW in dryer. In addition, the main contribution of this study is that the solar-assisted multi-generation systems have good potential in terms of energy and exergy efficiency. Highlights: A new solar energy assisted multi-generation system is developed. Overall energy and exergy efficiencies of system are evaluated. Energetic and exergetic performance of the overall study are calculated as 48.19% and 43.57%. The highest rate of irreversibility has the parabolic dish collector sub-system.